Association between abusive supervision and nurses’ withholding voice about patient safety: the roles of impression management motivation and speak up-related climate - Zhi-Ying Li; Yu-Pei Yang; Qian Wang; Mei-Xian Zhang; Cheng-Wen Luo; Ling-Feng Zhu; Tao-Hsin Tung; Hai-Xiao Chen (BMC Nursing, 2024)
Abstract Background Abusive supervision by the nurse manager significantly influences nurses’ withholding voice about patient safety. The role of impression management motivation and speak up-related climate is crucial in understanding their connection. This study aimed to explore the relationship between abusive supervision, impression management motivation, speak up-related climate, and withholding voice about patient safety. Methods This cross-sectional study employed a convenience sampling method to recruit 419 clinical nurses from Taizhou Hospital, Zhejiang Province, China, between 1 November 2022 and 31 January 2023. The study adhered to the STROBE checklist. Abusive supervision and impression management motivation were assessed using the Chinese versions of the Abusive Supervision Scale and the Impression Management Motivation Scale, respectively. Withholding voice about patient safety and speak up-related climate were identified using the Chinese version of the Speaking Up about Patient Safety Questionnaire. Results Nurse leaders’ abusive supervision (β=0.40, p<0.01) and nurses’ impression management motivation (β=0.10, p<0.01) significantly and positively influenced nurses’ withholding voice about patient safety. We introduced impression management motivation as a mediating variable, and the effect of abusive supervision on nurses’ withholding voice decreased (β from 0.40 to 0.38, p< 0.01). Nurses’ speak up-related climate played a moderating role between abusive supervision and impression management motivation (β= 0.24, p<0.05). Conclusions Abusive supervision by nursing leaders can result in nurses withholding voice about patient safety out of self-protective impression management motives. This phenomenon inhibits nurses’ subjective initiative and undermines their proactive involvement in improving patient safety, and hinders the cultivation of a culture encouraging full participation in patient safety, which should warrant significant attention.